Working Capital Management and Its Impact on Profitability: A Study of Selected Listed Beverage, Food and Tobacco Companies in Colombo Stock Exchange, Sri Lanka - Anojan, V.; Arulalan, N.; Nimalathasan, B. (The International Journal Of Business & Management, 2013)
The main purposes of this study are to identify significant impact on Working Capital Management (WCM) on profitability and find out the relationship between WCM and profitability of selected listed Beverage, Food and Tobacco Companies in Colombo Stock Exchange (CSE) from the financial year 2008 to 2012. Regression and Correlation analysis were performed in this study. According to the correlation results of this study stated that there is no significant relationship between WCM and profitability of Beverage, Food and Tobacco companies in Sri Lanka. Debtor’s, Creditor’s and inventory conversion period have a negative relationship on return on assets as well Creditor Conversion Period (CCP) has a negative relationship with Gross Profit (GP), it means if the CCP arise or increase that will reduce GP of the company. Regression analysis results revealed that there is no significant impact of WCM on profitability of the selected listed Beverage, Food and Tobacco Companies in Colombo Stock Exchange (CSE). The findings show that WCM has a negative relationship Return on Assets (ROA) of the companies, it is concluded to the managers need to maintain or keep their working capital components at an optimum level to achieve their expecting profitability of the firm and competitive advantage in the market.
Keywords: Working Capital Management (WCM); Profitability; Listed Companies; Beverage Food & Tobacco